If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 4 = 2 + 4c Reorder the terms: 4 + 3x = 2 + 4c Solving 4 + 3x = 2 + 4c Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 3x = 2 + -4 + 4c Combine like terms: 4 + -4 = 0 0 + 3x = 2 + -4 + 4c 3x = 2 + -4 + 4c Combine like terms: 2 + -4 = -2 3x = -2 + 4c Divide each side by '3'. x = -0.6666666667 + 1.333333333c Simplifying x = -0.6666666667 + 1.333333333c
| 4-2w=7-3w | | 3x-6=27+6x | | 15n+10n=25n+50 | | 217-6x=39x+17 | | B+P+A=C | | -6x-2=6x-134 | | 40n=20n+40 | | 2y-10=3y+5 | | 8-8x=131-29x | | 10x^2+51x+56=0 | | -7x+1=4x-87 | | 15+25x=265 | | w(w-3)=40 | | 3y+5=2y-10 | | 5(3x+7)=80 | | 13=7x-2x+3 | | 10=5n+45 | | 66=-20x+6 | | 3x^2+10=40 | | 15n=30 | | 36=-3x+6x+9 | | 4u^2+v+2uv+2u= | | 8n+4n=25-1n | | -12*12=X | | -6x-9=23+2x | | 10y+4=11y-2 | | 10+2t-5s-st= | | 3x+16=10x-14 | | 3x+16=10-14 | | 2y+3x=0 | | 5c+3-2c=36 | | 4x^2+12x+9=5x^2 |